Perancangan Tata Letak Fasilitas pada Area Inspecting Menggunakan Metode Activity Relationship Chart (ARC) di PT X - Annida Haya Fadhilah; Bekti Nugrahadi; Anita Oktaviana Trisna Devi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
PT. X is a textile company that produces greige fabric. One of the crucial stages in the greige fabric production process is inspection. Currently, the facility layout of the inspection area at PT X is still suboptimal. This results in longer fabric movement distances and increased time, leading to delivery delays and higher material handling costs. This study aims to design an optimal facility layout in the inspection area using the Activity Relationship Chart (ARC) method and to determine the distances, times, and costs for the proposed layout. In the initial production layout, the fabric movement distance reached 26,130 meters in one working day, and the fabric movement time was 936 minutes. Furthermore, the initial production layout generated a relatively high OMH of Rp 13,742,980 per month. After designing the facility layout using the Activity Relationship Chart (ARC) and Blockplan methods, the proposed layout was arranged according to the production process sequence, resulting in a smoother material flow. The proposed layout yields 16,830 meters of fabric movement per workday, 660 minutes of required time, and a monthly OMH of Rp 7,945,622, with an efficiency of 39.32%.